PRESENT AND PROSPECTS EARLY CARE IN THE CZECH REPUBLIC EXAMPLES OF GOOD PRACTICE FROM THE PARDUBICE REGION - Šándorová, Zdenka; Jirava, Pavel (My University, 2014)
Theme of support and assistance to family with "a risk" child in early age is a topic of current in the Czech Republic and in the European context. This paper is focused on this theme and aim is introduction of social prevention of early care in the Czech Republic, including an example of "good practice" - a particular provider of early intervention in the Pardubice region. Longitudinal research on this particular provider gives the possibility to analyze the selected data. The conclusion of the research confirms the validity and effectiveness of services for very vulnerable target group - a family with a child early age with limited options socialization due to disability (sensory, mental, communication or combined).
SOUČASNOST A PERSPEKTIVY RANÉ PÉČE V ČESKÉ REPUBLICE, PŘÍKLAD DOBRÉ PRAXE Z PARDUBICKÉHO KRAJE
Keywords: Child at risk; social prevention; early care; data; time series; Ohrožené dítě; služba sociální prevence; raná péče; data; časové řady.